Pengembangan PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ESD CARD & SPIN BOARD MATERI PECAHAN UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA SEKOLAH DASAR - Niken Ayu Pratiwi Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop learning media based on ESD Card and Spin Board fraction material to improve problem-solving abilities of elementary school students. The development model used is 4D (Define, Design, Develop, and Disseminate). This media is designed by integrating the sustainability context of the seven pillars of SDGs, namely (SDG 1) No Poverty, (SDG 2) Zero Hunger, (SDG 3) Healthy and Prosperous Life, (SDG 6) Clean Water and Adequate Sanitation, (SDG 7) Clean and Affordable Energy, (SDG 12) Responsible Consumption and Production, (SDG 15) Terrestrial Ecosystems. The study was conducted at SDN Sukaresmi 06 involving 35 fourth-grade students. The research instruments consisted of expert validation questionnaires, teacher and student response questionnaires, and pretest and posttest tests. The validation results by three experts (material, media, and language) showed a Content Validity Index (CVI) value of 1.00 and a Content Validity Ratio (CVR) of 1.00, indicating that this media is very valid. Student responses to the media showed a practicality percentage of 98.63%, included in the very practical category. To determine the effectiveness of the media, an N-Gain test was conducted. The results showed that the average N-Gain data for students was 0.82, included in the high category, indicating a significant increase in students' problem-solving abilities. Based on these results, it can be concluded that the ESD-based card and spin board learning media is valid, practical, and effective in improving elementary school students' problem-solving abilities, and is able to instill sustainability values in contextual mathematics